THE EFFECT OF EDUCATION AND TRAINING ON THE COMPETENCY OF POLICE PERSONNEL RESERSE POLRES KAMPAR - Dedi Antoni (STIE Bangkinang Publishing, 2022)
This study aims to determine the effect of education and training simultaneously and partially on the competence of the police personnel of the Kampar Police Criminal Investigation Unit. The analysis used in this study is multiple linear analysis with a population of 39 personnel. The entire population is sampled. Hypothesis testing is done using the f test and t test. Based on the research results, it can be concluded that simultaneously and partially education and training have an effect on competence. The closeness of the relationship between the independent variable and the dependent variable is very strong with the contribution of the independent variable to the dependent variable of 73.70%.